2018
DOI: 10.1101/252148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Receptive field center-surround interactions mediate context-dependent spatial contrast encoding in the retina

Abstract: SummaryAlmost every neuron in the early visual system has some form of an antagonistic receptive field surround. But the function of the surround is poorly understood, especially under naturalistic stimulus conditions. Anatomical and functional characterization of the surround of retinal ganglion cells suggests that surround signals combine with the excitatory feedforward pathway upstream of an important synaptic nonlinearity between bipolar cells and postsynaptic ganglion cells. This circuit architecture sugg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…First, the assumptions of the SNMF algorithm are not directly matched to the structure of the subunit response model: the present model assumes nonnegative subunit outputs, while the SNMF factorization method assumes that the subunit filters themselves are nonnegative. The assumption of nonnegative filters is inconsistent with suppressive surrounds previously reported in retinal bipolar cells ( Dacey et al, 2000 ;Fahey & Burkhardt 2003;Turner et al, 2018), and limits the application of the method to other systems such as V1 (Figure 8). However, a recent modification of the SNMF method applies non-negativity constraints on subunit weights instead of the subunit filters (Jia et al, 2018), making it more suitable for other applications.…”
Section: Modeling Linear-nonlinear Cascadesmentioning
confidence: 89%
See 1 more Smart Citation
“…First, the assumptions of the SNMF algorithm are not directly matched to the structure of the subunit response model: the present model assumes nonnegative subunit outputs, while the SNMF factorization method assumes that the subunit filters themselves are nonnegative. The assumption of nonnegative filters is inconsistent with suppressive surrounds previously reported in retinal bipolar cells ( Dacey et al, 2000 ;Fahey & Burkhardt 2003;Turner et al, 2018), and limits the application of the method to other systems such as V1 (Figure 8). However, a recent modification of the SNMF method applies non-negativity constraints on subunit weights instead of the subunit filters (Jia et al, 2018), making it more suitable for other applications.…”
Section: Modeling Linear-nonlinear Cascadesmentioning
confidence: 89%
“…Second, the assumption of space-time separable RGC subunits significantly reduces the number of parameters that need to be estimated, but could be relaxed with more data. For example, a rank 2 approximation that allows for separate space-time separable center and surround filters for each subunit may be useful (Schweitzer-Tong, Enroth-Cugell & Pinto, 1970 ), given the center-surround structure of bipolar cell receptive fields (Dacey et al, 2000, Turner et al, 2018.…”
Section: Further Applications and Extensionsmentioning
confidence: 99%
“…Finally, many standard models of visual responses in retinal ganglion cells assume linear receptive fields and thus linear integration of visual signals. Yet, recent studies have emphasized the importance of incorporating nonlinear signal integration, in particular nonlinear spatial integration, to predict the responses of ganglion cells to natural stimuli (Heitman et al, 2016;Liu et al, 2017;Shah et al, 2020;Turner and Rieke, 2016;Turner et al, 2018). Commonly, such models are fitted to responses from achromatic (grayscale) stimuli, and it will be interesting to explore how to include nonlinear chromatic integration for predicting response to chromatic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of spatial integration, in particular, refined the idea of receptive fields (Barlow, 1953;Hartline, 1938) and later resulted in the distinction of linear and nonlinear spatial integration, as originally exemplified by the X and Y cells of the cat retina (Enroth-Cugell and Freeman, 1987;Enroth-Cugell and Robson, 1966;Hochstein and Shapley, 1976). Mechanistic investigations of spatial integration then elucidated the role of retinal bipolar cells in shaping signal transmission through the retina (Bolinger and Gollisch, 2012;Borghuis et al, 2013;Demb et al, 2001;Schwartz et al, 2012;Turner and Rieke, 2016) and helped characterize the suppressive receptive field surround (Barlow, 1953;Kuffler, 1953;Takeshita and Gollisch, 2014;Turner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a non-linear interaction between the center and surround parts of the RF in RGCs modulates the response to spatial patterns in a context-dependent manner, and that this effect is greater during naturalistic stimulation 50 . We think that this effect can explain, at least in part, the results that we observe; the additional signals contained in the complex stimulus would act as non-linear inhibitors, resulting in lower response when the parameters are farther from the preference of the cell, producing narrower tuning curves.…”
Section: Discussionmentioning
confidence: 99%